If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (3 + i)(3 + -1i)(2 + 6i) = 0 Multiply (3 + i) * (3 + -1i) (3(3 + -1i) + i(3 + -1i))(2 + 6i) = 0 ((3 * 3 + -1i * 3) + i(3 + -1i))(2 + 6i) = 0 ((9 + -3i) + i(3 + -1i))(2 + 6i) = 0 (9 + -3i + (3 * i + -1i * i))(2 + 6i) = 0 (9 + -3i + (3i + -1i2))(2 + 6i) = 0 Combine like terms: -3i + 3i = 0 (9 + 0 + -1i2)(2 + 6i) = 0 (9 + -1i2)(2 + 6i) = 0 Multiply (9 + -1i2) * (2 + 6i) (9(2 + 6i) + -1i2 * (2 + 6i)) = 0 ((2 * 9 + 6i * 9) + -1i2 * (2 + 6i)) = 0 ((18 + 54i) + -1i2 * (2 + 6i)) = 0 (18 + 54i + (2 * -1i2 + 6i * -1i2)) = 0 (18 + 54i + (-2i2 + -6i3)) = 0 (18 + 54i + -2i2 + -6i3) = 0 Solving 18 + 54i + -2i2 + -6i3 = 0 Solving for variable 'i'. Factor out the Greatest Common Factor (GCF), '2'. 2(9 + 27i + -1i2 + -3i3) = 0 Ignore the factor 2.Subproblem 1
Set the factor '(9 + 27i + -1i2 + -3i3)' equal to zero and attempt to solve: Simplifying 9 + 27i + -1i2 + -3i3 = 0 Solving 9 + 27i + -1i2 + -3i3 = 0 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.
| (5+i)(5-i)(6+2i)= | | 5-6n=23 | | 35=-7(z+3) | | 5-5n=23 | | i(4+3i)(4-3i)= | | 4x+7=-37-7x | | 17-2m=21 | | i(9+6i)(9-6i)= | | 89-3x=33x+21 | | 6-7x=36-21x | | 8-v=13 | | (2+i)(2-i)= | | -111-10x=8x+15 | | 30-2x=0 | | 11-4u=3 | | 2a+11-11a+33= | | 600+0.8x=720x | | 26-5z=11 | | 4.6x-2.6=x-3 | | 28-3y=10 | | 4x^2+8x=140 | | x^3=100x | | (4-8i)(4-8i)= | | 3x+8=62-3x | | 16-x=9 | | (6-8i)(6-8i)= | | 7x^2-6x=1 | | -7(t-7)=-14 | | 3v^2=8v | | s^2=16 | | 8y+7=15y+7 | | (6+4i)(5+i)= |